GAMBARAN AKTIVITAS FISIK PASIEN DIABETES MELLITUS DI MASA PANDEMI COVID-19 - Isnarawati, Zakianor; Diani, Noor; Agianto, Agianto (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022DO - 10.24843/coping.2022.v10.i04.p14, 2022)
Diabetes mellitus is one of the main risk factors for susceptibility to Covid-19 infection with uncontrolled blood sugar levels. In patients with diabetes mellitus, physical activity is one of the pillars of diabetes mellitus management which functions to improve insulin sensitivity and also maintain body fitness. The purpose of this study was to describe the level of physical activity of patients with diabetes mellitus during the Covid-19 pandemic in Banjarmasin. The research design used a quantitative descriptive research with non-probability sampling technique with a total sampling type involving 44 diabetes mellitus patients as respondents. Using the Physical Activity Questionnaires (IPAQ) questionnaire instrument. Data analysis using descriptive analysis with results that show a description of the physical activity of diabetes mellitus patients in the Covid-19 pandemic in Banjarmasin from 44 respondents 10 respondents (22,7%) low physical activity, 17 respondents (36,6%) moderate physical activity, and 17 respondents (36,6%) had strenuous physical activity. Physical activity of patients with diabetes mellitus in the Covid-19 pandemic has shown an increase. The expected physical activity in the patient is in accordance with the recommendations, namely the patient with diabetes mellitus is active with physical activity with a moderate to severe level of physical activity according to the ability and condition of the patient, both activities carried out related to work, transportation, domestic activities, activities on time relaxed, and sitting time at least 10 minutes in one activity in the span of the last week.